Novel Biomaterial for Artery Patch in Swine Model With High-Fat Diet - Lu, Xiao; Han, Ling; Guo, Xiaomei; Wang, Mengjun; Baradarian, Sam; Golts, Eugene; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2021)
Objective We evaluated swine and bovine pulmonary visceral pleura (PVP) in artery patch-angioplasty in swine model of high-fat diet. Background Arterial patch-angioplasty is frequently used for repair or reconstruction of arteries. An autologous patch is often limited by the number and dimension of donor tissue and can result in donor complications. Furthermore, mechanical mismatch is a cause of poor performance of vascular reconstruction. Here, we introduce a readily available patch biomaterial with similar compliance as native arteries. Methods The PVP was peeled from swine and bovine lungs by hydro-dissection. The swine and bovine PVPs were crosslinked with glutaraldehyde and then sterilized. The swine PVP (sPVP) patches were implanted in the carotid and femoral arteries of six Yorkshire pigs that were fed a regular diet and euthanized at 2 and 4 months postoperative. The bovine PVP (bPVP) patches were implanted in the carotid artery of six Yucatan pigs that were fed a high-fat diet and euthanized at 4 months postoperative. Patency was evaluated by ultrasound and angiography. Neo-endothelium and media were evaluated by histologic examination. Results All arteries in patch-angioplasties remained patent with no adhesions, inflammation, or aneurysms. Biomarkers of endothelial cells (e.g., Factor VIII and eNOS) were detected in the neo-endothelial cells. We observed endothelial cell–cell junctions in the confluent neo-endothelium in the PVP patches. Neo-media composed of vascular smooth muscle developed similar as native arteries. In the hypercholesterolemic model, we observed the accumulation of cholesterol in both arterial tissues and in the neo-vascular tissues in the PVP patches. Protein expressions of lipid transport and metabolism (e.g., APOE-1, ABCA, and PACK9) were also observed in both arterial and neo-vascular tissues. Conclusion The PVP patch-angioplasty overcomes the pitfalls of compliance mismatch of synthetic patches and has a non-thrombogenic surface. The proliferation of vascular cells assembled to generate the neo-endothelium and media in the patch-angioplasties to support long-term patency. The neo-vascular tissue in PVP patch-angioplasty also developed similar cellular functions for lipid transport and metabolism compared with native arteries in hypercholesterolemia.